Effect of chitosan nanoparticles on quorum sensing-controlled virulence factors and expression of LasI and RhlI genes among Pseudomonas aeruginosa clinical isolates - Rana Abdel Fattah Abdel Fattah; Fatma El zaharaa Youssef Fathy; Tahany Abdel Hamed Mohamed; Marwa Shabban Elsayed (AIMS Microbiology, 2021)
Antibiotic-resistant strains of Pseudomonas aeruginosa (P. aeruginosa) pose a major threat for healthcare-associated and community-acquired infections. P. aeruginosa is recognized as an opportunistic pathogen using quorum sensing (QS) system to regulate the expression of virulence factors and biofilm development. Thus, meddling with the QS system would give alternate methods of controlling the pathogenicity. This study aimed to assess the inhibitory impact of chitosan nanoparticles (CS-NPs) on P. aeruginosa virulence factors regulated by QS (e.g., motility and biofilm formation) and LasI and RhlI gene expression. Minimum inhibitory concentration (MIC) of CS-NPs against 30 isolates of P. aeruginosa was determined. The CS-NPs at sub-MIC were utilized to assess their inhibitory effect on motility, biofilm formation, and the expression levels of LasI and RhlI genes. CS-NPs remarkably inhibited the tested virulence factors as compared to the controls grown without the nanoparticles. The mean (±SD) diameter of swimming motility was decreased from 3.93 (±1.5) to 1.63 (±1.02) cm, and the mean of the swarming motility was reduced from 3.5 (±1.6) to 1.9 (±1.07) cm. All isolates became non-biofilm producers, and the mean percentage rate of biofilm inhibition was 84.95% (±6.18). Quantitative real-time PCR affirmed the opposition of QS activity by lowering the expression levels of LasI and RhlI genes; the expression level was decreased by 90- and 100-folds, respectively. In conclusion, the application of CS-NPs reduces the virulence factors significantly at both genotypic and phenotypic levels. These promising results can breathe hope in the fight against resistant P. aeruginosa by repressing its QS-regulated virulence factors.